Strategi Promosi Dompet Elektronik Balipay terhadap Usaha Mikro Kecil dan Menengah - Putra, I Gusti Agung Ananda; Sadewa, Komang Okky Junior (LPPM Universitas Bumigora, 2024)
Digital wallets are both an opportunity and a threat to the banking industry. Nowdays, banks are starting to enter digital wallets to adapt, including Bali Regional Development Bank. The bank launches of its digital wallet product, namely Balipay. It faces a big challenge because it has just entered a market that is already very competitive. This service activity aims to develop a market access strategy for the Balipay e-wallet product by taking into account the identified problems, so that the product can be accepted in the market using digital marketing methods, communication strategy, and providing flyers. After the socialization, business owners' knowledge of the benefits of e-wallets as promotional content and increasing consumer purchasing power will increase and have a sense of interest in registering their business to Balipay products. In this regard, the right strategy is needed so that the Balipay e-wallet product can be accepted by the public. It has a good impact on people to use Balipay products.